(untitled) (GAIMS Journal of Medical Sciences, 2026)
Cystic Encephalomalacia refers to the destruction of brain tissue following cerebral infarction and ischemia, infection, head trauma, or other injury. Cystic encephalomalacia (CE) is a most rare disease in adults. Though multiple causative factors come into play, hyperhomocysteinemia is now regarded as a potent aetiology. Here, we describe a 48-year-old male with previous history of cerebrovascular accident (CVA) who was admitted with multiple episodes of seizures. MRI showed chronic infarcts with cystic encephalomalacia changes, and metabolic screening demonstrated elevated levels of homocysteine. This is a case showing the significance of metabolic factors in ischemic cerebral injury and early screening. Differential diagnosis of CE from other changes due to ischemia is of paramount importance to ensure proper treatment and prognosis.